3,3-dimethyl-octane from Physalis peruviana as promising anti-DENV via ADMET prediction of pkCSM open webserver - Prastiyanto, Muhammad Evy; Solekha, Rofiatun; Rohmah, Laila Ainur; Yuanita Rachmawati; Aini, Nur Sofiatul (Genbinesia Journal of Biology, 2023)
Dengue is caused by the dengue virus (DENV) and being prevalent in 100 tropical and subtropical countries including Indonesia. This disease is spread by Aedes mosquitoes. There is currently no clinically authorized medicine to treat the dengue fever. Physalis peruviana has ethnomedicine application and noted for its antioxidant activities. This study purpose to investigate the pharmacokinetics or ADMET of anti-DENV from leaf parts of P. peruviana. The phytoconstituents data were gathered from multiple sources. The drug property and ADMET prediction were assessed using pkCSM. Following online screening, 3,3-dimethyl-octane functioned as predictive anti-DENV therapeutic candidate. Further dry and wet lab studies are needed to validate this finding.